2015
DOI: 10.1016/j.cmi.2014.08.020
|View full text |Cite
|
Sign up to set email alerts
|

The aetiology of pharyngotonsillitis in adolescents and adults – Fusobacterium necrophorum is commonly found

Abstract: Sore throat is common in primary healthcare. Aetiological studies have focused on the presence of a limited number of pathogens. The aim of the present study was to investigate the presence of a wide range of bacteria and viruses, including Fusobacterium necrophorum, in patients with pharyngotonsillitis and in asymptomatic controls. A prospective case control study was performed in primary healthcare in Kronoberg County, Sweden. Patients (n=220) aged 15 to 45 years with a suspected acute pharyngotonsillitis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
34
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 25 publications
(39 reference statements)
6
34
1
2
Order By: Relevance
“…9,47,48 Recent studies point to a major role of F necrophorum in PTA, 4,9,10 and this anaerobe may also play a pathogenic role in acute tonsillitis. [49][50][51][52] This concordance of 2 significant pathogens between PTA and acute tonsillitis lends further support to the acute tonsillitis hypothesis. However, it can be argued that bacteria can exert their pathogenic potential at different anatomic sites without causal relationship.…”
Section: Findings Supporting the Acute Tonsillitis Hypothesissupporting
confidence: 62%
“…9,47,48 Recent studies point to a major role of F necrophorum in PTA, 4,9,10 and this anaerobe may also play a pathogenic role in acute tonsillitis. [49][50][51][52] This concordance of 2 significant pathogens between PTA and acute tonsillitis lends further support to the acute tonsillitis hypothesis. However, it can be argued that bacteria can exert their pathogenic potential at different anatomic sites without causal relationship.…”
Section: Findings Supporting the Acute Tonsillitis Hypothesissupporting
confidence: 62%
“…3 Most of the throat swabs were from Viborg Hospital (Middle part of Central Jutland). 4 Most of the peritonsillar abscess were from Skejby Hospital (Eastern part of Central Jutland).…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence suggests that Fusobacterium necrophorum can cause acute and recurrent tonsillitis (1)(2)(3)(4)(5)(6). F. necrophorum tonsillitis can progress to peritonsillar abscess (PTA) and, although rarely, to Lemierre's syndrome, a life-threatening metastatic septicaemia in youngsters (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…They found higher percentages of patients with Group C streptococcus (3.6% vs 0.8%, P = .16) and F necrophorum (15.0% vs 3.1%, P = .001) in the symptomatic patients, ratios similar to those for Group A streptococcus (30% vs 2.3%, P <.001) and rhinovirus (6.4% vs 2.3%, P = .09). 27 Another found F necrophorum in 14 of 85 university students with sore throat (16.5%), compared with 29 of 326 who were asymptomatic (8.9%). 21 Most recently, Centor and colleagues found higher rates of both F necrophorum (20.5% vs 9.4%) and Group C streptococcus (9.0% vs 3.9%) in university students with sore throat than in asymptomatic controls.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the study characteristics: 6 reported the prevalence of Group C streptococcus, 4,5,[17][18][19][20] 3 the prevalence of F necrophorum, 16,21,22 and 7 the prevalence of both pathogens. 7,10,[23][24][25][26][27] Data collection ranged from 2000 to 2014 and took place in 9 countries.The prevalence of Group C streptococcus is summarized in the forest plot in Figure 2. The overall prevalence of Group C streptococcus was 6.1% (95% CI, 3.2%-9.0%) with a range from 0.5% 14 to 24.8%.…”
mentioning
confidence: 99%